Effect of Blocking Screws on Union of Infraisthmal Femur Fractures Stabilized With a Retrograde Intramedullary Nail. Issue 5 (May 2018) - Van Dyke, Bryan; Colley, Ryan; Ottomeyer, Christina; Palmer, Ryan; Pugh, Kevin
Abstract : Objective: To investigate the effect of blocking screws (BS) on the union rate and stability of infraisthmal femur fractures treated with retrograde intramedullary nail (RIMN) insertion. Design: Retrospective cohort study. Setting: A single level 1 trauma center. Patients/Participants: All patients with an infraisthmal femur fracture treated with a RIMN from 2005 to 2012 were included. Intervention: All fractures were treated with a RIMN. BS were used at the discretion of the treating surgeon. Main Outcome Measurements: (1) Radiographic time to union, (2) initial postoperative sagittal and coronal angulation, and (3) final sagittal and coronal angulation. Results: Neither the average time to union (BS 21.1 weeks vs. 21.8 weeks), nor union rates (BS 61% vs. 77%) were statistically different between BS and non-BS constructs. No significant alignment differences existed whether BS were used or not. Conclusions: In this study, we were not able to verify our hypothesis. In fact, we did not find any significant advantages when BS were added to a RIMN construct for distal femur fractures with respect to union time, union rate, or improvements in alignment. Additional studies are needed to determine the actual benefit of BS in the treatment of infraisthmal femoral shaft fractures treated with retrograde intramedullary nailing. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.